A new solution algorithm for solving rule‐sets based bilevel decision problems. (29th March 2012) - Lu, Jie; Zheng, Zheng; Zhang, Guangquan; He, Qing; Shi, Zhongzhi; Hussain, Farookh Khadeer; Wyrzykowski, Roman; Tudruj, Marek
Summary Bilevel decision addresses compromises between two interacting decision entities within a given hierarchical complex system under distributed environments. Bilevel programming typically solves bilevel decision problems. However, formulation of objectives and constraints in mathematical functions is required, which are difficult, and sometimes impossible, in real‐world situations because of various uncertainties. Our study develops a rule‐set based bilevel decision approach, which models a bilevel decision problem by creating, transforming and reducing related rule sets. This study develops a new rule‐sets based solution algorithm to obtain an optimal solution from the bilevel decision problem described by rule sets. A case study and a set of experiments illustrate both functions and the effectiveness of the developed algorithm in solving a bilevel decision problem. Copyright © 2012 John Wiley & Sons, Ltd.